The challenges of shared decision making in dementia care networks. (9th September 2016) - Groen-van de Ven, Leontine; Smits, Carolien; Span, Marijke; Jukema, Jan; Coppoolse, Krista; de Lange, Jacomine; Eefsting, Jan; Vernooij-Dassen, Myrra
ABSTRACT: Background: Decision making is an important part of managing one's life with dementia. Shared decision making is the preferred way of involving people in decisions. Our study aimed to describe the challenges of shared decision making in dementia care networks. Methods: A multi-perspective qualitative study using face-to-face interviews with 113 respondents in 23 care networks in the Netherlands consisting of 23 people with dementia, 44 of their informal caregivers, and 46 of their professional caregivers. The interview guide addressed the decision topics, who were involved in the decision making and their contributions to the decision making. We used content analysis to delineate categories and themes. Results: The themes and categories that emerged are: (1) adapting to a situation of diminishing independence, which includes the continuous changes in the care network, resulting in shifting decision-making roles and the need for anticipating future decisions; and (2) tensions in network interactions which result from different perspectives and interests and which require reaching agreement about what constitutes a problem by exchanging information in the care network. Conclusion: The challenges in dementia care networks relate to all dimensions of social health. They have implications for a model of shared decision making in dementia care networks. Such a model requires flexibility regarding changing capabilities to preserve the autonomy of the person with dementia. It needs working towards a shared view about what constitutes a problem in the situation. It asks for professionals to advocate for the involvement of people with dementia by helping them participate in ways that strengthen their remaining capacities.